CLINOSTOMOIDES PANDEYII N. SP., A RARE CLINOSTOME METACERCARIA FROM HETEROPNEUSTES FOSSILIS (BLOCH) - SINGH, H.S.; SHARMA, BINDU (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1994)
The present communication deals with a new species of metacercaria, Clinostomoides Dollfus, 1950, from the body cavity of H. fossilis (Bloch). The present form is characterised by having spinose body, different positions of gonads, gonopore and difference in arrangement of uterus.